Sexuality, gender and schooling : shifting agendas in social learning - Kehily, Mary Jane (Routledge, 2002)
Young people tend to find themselves learning about sexuality and gender in their social settings. What implications does this have for their teachers and for the development of policy and practice in personal, social and health education? This book takes a look at the issues.